2023
DOI: 10.5194/bg-2023-119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving heterogeneous fluxes from tundra halves the growing season carbon budget

Abstract: Abstract. Landscapes are often assumed to be homogeneous when interpreting eddy covariance fluxes, which can lead to biases when gap-filling and scaling-up observations to determine regional carbon budgets. Tundra ecosystems are heterogeneous at multiple scales, with variation in plant functional types, soil moisture, thaw depth, and microtopography, for example, influencing net ecosystem exchange (NEE) of carbon dioxide (CO2) and methane (CH4) fluxes. With warming temperatures, Arctic ecosystems could change … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Also consistent with prior research 23 , we observed that median bryophyte and shrub aboveground biomass were consistently higher than median lichen, herb, or tree aboveground biomass, with bryophytes comprising the largest proportion of total aboveground biomass in the High Arctic and shrubs the largest proportion in the Low Arctic. However, it is important to note there is high spatial variability in the amount and composition of plant aboveground biomass among field sites in each bioclimatic zone, reflecting pronounced heterogeneity within and among vegetation communities 61 , 62 .…”
Section: Technical Validationmentioning
confidence: 99%
“…Also consistent with prior research 23 , we observed that median bryophyte and shrub aboveground biomass were consistently higher than median lichen, herb, or tree aboveground biomass, with bryophytes comprising the largest proportion of total aboveground biomass in the High Arctic and shrubs the largest proportion in the Low Arctic. However, it is important to note there is high spatial variability in the amount and composition of plant aboveground biomass among field sites in each bioclimatic zone, reflecting pronounced heterogeneity within and among vegetation communities 61 , 62 .…”
Section: Technical Validationmentioning
confidence: 99%